ANALISIS RASIO LIKUIDITAS DAN PROFITABILITAS UNTUK MENGUKUR KINERJA KEUANGAN PADA PT ULTRAJAYA MILK INDUSTRY & TRADING COMPANY TBK PERIODE 2014 -2023 - Wahyudi, Ichsan; Hendra, Dede (Journal of Research and Publication Innovation, 2024)
This research aims to determine the condition of the financial performance of the company PT Ulta Jaya Milk Industry & Trading Company Tbk in the period 2014 to 2023 using financial ratio measuring instruments. The research method used is a quantitative descriptive method, because this research is related to the research object, namely the company within a certain period of time by collecting data and information related to the company and adjusted to the research objectives. The data analysis method used is ratio analysis which describes the relationship between certain amounts and other amounts. The analysis used is liquidity and profitability where the liquidity ratio aims to determine the company's ability to fulfill its short-term obligations. Meanwhile, the profitability ratio is the company's ability to generate profits during a certain period. From the research results using the liquidity ratio from 2014-2023, it can be seen from the company's current ratio that it is in a healthy condition because the average value is 378% above the manufacturing industry standard of 200%. Judging from the Quick Ratio, the company is in healthy condition because the average value is 266% above the manufacturing industry standard of 150%. Meanwhile, using the profitability ratio from 2014-2023, it can be seen from the Net Profit Margin that the company is in an unhealthy condition because the average value is 15% below the manufacturing industry standard of 20%. Judging from the Return on Assets, the company is in an unhealthy condition because the average value is 13% below the manufacturing industry standard of 30%.